Endothelial Differentiation of Human Adipose-Derived Stem Cells on Polyglycolic Acid/Polylactic Acid Mesh. (28th May 2015) - Deng, Meng; Gu, Yunpeng; Liu, Zhenjun; Qi, Yue; Ma, Gui E.; Kang, Ning
Abstract : Adipose-derived stem cell (ADSC) is considered as a cell source potentially useful for angiogenesis in tissue engineering and regenerative medicine. This study investigated the growth and endothelial differentiation of human ADSCs on polyglycolic acid/polylactic acid (PGA/PLA) mesh compared to 2D plastic. Cell adhesion, viability, and distribution of hADSCs on PGA/PLA mesh were observed by CM-Dil labeling, live/dead staining, and SEM examination while endothelial differentiation was evaluated by flow cytometry, Ac-LDL/UEA-1 uptake assay, immunofluorescence stainings, and gene expression analysis of endothelial related markers. Results showed hADSCs gained a mature endothelial phenotype with a positive ratio of 21.4 ± 3.7% for CD31+/CD34− when induced in 3D mesh after 21 days, which was further verified by the expressions of a comprehensive range of endothelial related markers, whereas hADSCs in 2D induced and 2D/3D noninduced groups all failed to differentiate into endothelial cells. Moreover, compared to 2D groups, the expression for α -SMA was markedly suppressed in 3D cultured hADSCs. This study first demonstrated the endothelial differentiation of hADSCs on the PGA/PLA mesh and pointed out the synergistic effect of PGA/PLA 3D culture and growth factors on the acquisition of mature characteristic endothelial phenotype. We believed this study would be the initial step towards the generation of prevascularized tissue engineered constructs.